Practical concurrent Haskell : with big data applications - Nita, Stefania Loredana; Mihailescu, Marius (Apress, 2017)
Teaching you how to use the APIs and frameworks for parallel and concurrent applications in Haskell, this book will show you how to exploit multicore processors with the help of parallelism in order to increase the performance of your applications. --